(untitled) (Bangladesh Critical Care Journal, 2013)
Background: Fatal outcome related risks are high when children with pneumonia present with severe acute malnutrition (SAM). However, data are limited on fatality related risk factors from pneumonia in Children with SAM especially those who attended in critical care ward. We evaluated clinically identifiable risks for fatal outcome in under-five Children with SAM with pneumonia at a critical care ward in an urban hospital. Methods: This study was of unmatched case-control design and Children with SAM of either sex, aged 0-59 months, admitted to the Intensive Care Unit (ICU) of Dhaka Hospital of the International Centre for Diarrhoeal Disease Research, Bangladesh (icddr,b) from April 2011 through July 2012 with radiological pneumonia were studied. The study children who had fatal outcome constituted the cases (n=35), and randomly selected children who survived constituted the controls (n=105). Results: The age (months) among the cases and the controls [median (inter-quartile range)] was comparable [8.0 (4.9, 11.0) vs. 9.7 (5.0, 18.0); p=0.210)]. In multivariate logistic regression analysis, after adjusting for potential confounders, such as abnormal mental status, vomiting, and systolic hypotension (<70 mm of Hg) in absence of dehydration, severely malnourished under-five children with pneumonia having fatal outcome more often had hypoxemia (OR=23.15, 95% CI=4.38-122.42), dehydrating (some/severe) diarrhea (OR=9.48, 95% CI=2.42-37.19), abdominal distension at admission (OR=4.41, 95% CI=1.12-16.52), and received blood transfusion (OR=5.50, 95% CI=1.21-24.99) for the management of crystalloid resistant systolic hypotension. Conclusion: The results of our data revealed hypoxemia, clinical dehydration, and abdominal distension as the independent risk factors for fatal outcome in Children with SAM with pneumonia. Severely malnourished children with pneumonia who required blood transfusion for the management of crystalloid resistant systolic hypotension were also at risk of fatal outcome. Thus, early identification and prompt management of these simple clinically recognizable risk factors for fatal outcome and avoiding the use of blood transfusion for the management of crystalloid resistant systolic hypotension may help reduce death in such population. DOI: http://dx.doi.org/10.3329/bccj.v1i2.17199 Bangladesh Crit Care J September 2013; 1 (2): 80-85